A simple, single-tube overlapping amplicon-targeted Illumina sequencing assay. - Jason D Limberis; Alina Nalyvayko; Joel D Ernst; John Z Metcalfe (PLoS ONE)
Targeted amplicon sequencing to identify pathogens, resistance-conferring mutations, and strain types is an important tool in diagnosing and treating infections. However, due to the short read limitations of Illumina sequencing, many applications require the splitting of limited clinical samples between two reactions. Here, we outline hairpin Illumina single-tube sequencing PCR (hissPCR) which allows for the generation of overlapping amplicons containing Illumina indexes and adapters in a single tube, effectively extending the Illumina read length while maintaining reagent and sample input requirements.